Leaving ADDIE for SAM field guide : guidelines and templates for developing the best learning experiences - Sites, Richard; Green, Angel (ASTD Press, 2014)
"Make your foray into successive approximations successful and as easy as possible. In the 2012 bestseller, Leaving ADDIE for SAM, learning professionals were introduced to the Successive Approximation Model (SAM) and the Savvy Start--the key to a successful project kick-off. Together, these concepts incorporate contemporary Agile processes that simplify design and development, yielding more energetic and effective learning experiences. This companion Field Guide provides the job aids, tools, and templates you need to put the SAM methodology in motion and take your ISD practice to new heights."--